Evaluate the quality of oral hygiene care in children with congenital cleft lip and palate in the course of orthodontic treatment - Filonenko В. В.; Bidenko Н. В. (Actual Dentistry, 2024)
Introduction. Systematic monitoring of the of oral hygiene and professional hygiene with the use of modern, individually selected basic and additional hygiene products and items during orthodontic treatment is a mandatory component of the comprehensive rehabilitation of children with congenital cleft lip and palate (CLP). The aim: to evaluate the quality of individual oral hygiene care of children with congenital unilateral cleft lip and palate in the course of orthodontic treatment in the period of transitional dentition. Materials and methods. The determination of the hygienic condition of the oral cavity in the course of orthodontic treatment was done using the «Differentiated index for determining the indicator of individual oral hygiene, adjusted to take into account the different quality of hygiene on the upper and lower dental rows (DIOH). Results and their discussion. Prevention of diseases of hard tissues of teeth and periodontal tissues in children is important from birth and is especially necessary in the course of orthodontic treatment using removable and fixed orthodontic designs. Children with CLP have an increased risk of developing dental caries for a variety of reasons. Differential examination of the state of dental hygiene on the upper and lower jaws allows giving more targeted recommendations regarding oral hygiene, i.e. personify them. Conclusions. The use of hygiene indices, in particular those that reflect the difference between the level of hygiene on the jaw where the orthodontic appliance is placed and where it is absent, is appropriate for assessing the state of oral hygiene in children with dentognathic anomalies and providing recommendations for its improvement.